Marketing Communications in Emerging Economies, Volume II Conceptual Issues and Empirical Evidence - Anning-Dorson, Thomas; Hinson, Robert E.; Coffie, Stanley; Bosah, Genevieve; Abdul-Hamid, Ibn Kailan (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Drawing on the expertise of multi-disciplinary scholars from emerging economies, this volume aims to share fascinating perspectives on marketing communications by discussing the shift in the power of public relations, and highlighting how the small and local use communication effectively to improve performance and shares useful lessons on how to communicate hope by responding to customer emotions during uncertainties. The book contains valuable lessons and insights on communicating corporate social responsibility, effective social media communication, enacting brand purpose through communication, and using aesthetics in point-of-purchase advertising to drive purchase intention. It is the first of its kind to highlight key conceptual issues and provide critical empirical evidence on marketing communications in and from emerging economies. Corporate executives, educators, students, policymakers and businesses would find this book a useful tool on marketing communication as it lays bare some important strategic and operational insights specific to emerging markets. Thomas Anning-Dorson (PhD) is an Associate Professor of Marketing at the University of the Witwatersrand, South Africa. Robert Ebo Hinson (PhD) is a Professor and Head of Department of Marketing and Entrepreneurship at the University of Ghana Business School. Stanley Coffie (PhD) is an Associate Professor of Marketing at the Ghana Institute of Management and Public Administration (GIMPA). Genevieve Bosah (PhD) is a Researcher and Lecturer at the Department of Media and Communications, University of Hertfordshire, UK. Ibn Kailan Abdul-Hamid (PhD) is a Lecturer at the University of Professional Studies, Accra, Ghana.
1. Traditional and Contemporary Notions of Marketing Communications -- 2. Power Shift: Analyzing the Changing Role of Public Relations in the Mar-keting Mix -- 3. Marketing Communication Planning for SMEs in Emerging Markets -- 4. Communicating Corporate Social Responsibility Initiatives: A focus on COVID-19 -- 5. Ithemba lila nyuka (Hope is Rising): Responding to Customer Emotions during Uncertainties - Kelebogile Makhafola and Thomas Anning-Dorson -- 6. Perception of Integrated Marketing Communications practice: Evidence from rural and community banks -- 7. Exploring Drivers of Performance in Advertising Firms in Ghana: A Per-spective of Attribution Theory -- 8. Using Social Media Communication to Enact Brand Purpose During A Global Health Pandemic -- 9. Aesthetics Response to Point-of- Purchase Advertising and Purchase Inten-tions of Groceries -- 10. Analyzing the Use of Social Media Communication Strategies in Indonesia and Malaysia: Insights and Implications -- 11. Integrated Marketing Communications in Emerging Economies - Conclusions and Recommendations. .
Keywords: Marketing; International economic integration; Globalization; Marketing; Emerging Markets and Globalization